Study Fenomenologi Terhadap Pengalaman Keluarga Dalam Merawat Anggota Keluarga Dengan Gangguan Jiwa Di Rumah - Dian Rahmi; Rikayoni; Anisa Febristi (Nan Tongga Health And Nursing, 2025)
Mental disorders are health conditions that affect how individuals think, feel, and behave. According to the World Health Organization (WHO, 2022), one in eight people reported a prevalence of schizophrenia or psychosis of 7 per mille. Mental disorders are health problems that not only affect individuals but also families as the primary caregivers. Families are responsible for ensuring medication adherence, assisting patients with daily activities, monitoring behavioral changes, and providing emotional support. This caregiving process is inseparable from various challenges, such as psychological burden, limited knowledge, social stigma, and barriers to accessing mental health services. Each family has different caregiving experiences. The heavy psychological burden experienced by families of people with mental disorders often leads to inadequate support provided to patients. This study aimed to explore the experiences of families in caring for a member with mental disorders at home. A qualitative approach with a phenomenological design was employed. Eight participants were selected through purposive sampling, with inclusion criteria of having a family member diagnosed with a mental disorder and living in the same household. Caring for a family member with a mental disorder imposes a multidimensional burden on families; however, they strive to endure through coping strategies and support from mental health nurses. The findings highlight the importance of family psychoeducation, family support groups, spiritual guidance, social advocacy, and community education to reduce stigma.